Pengaruh Service Quality, E- Trust adn Transformasi Digital terhadap Loyalitas Nasabah Pengguna Produk BSI Mobile: - Siti Fatimah (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This study aims to determine the Effect of Service Quality, E-trust and Digital Transformation on Customer Loyalty of BSI Mobile Product Users: Customer Satisfaction as an Intervening Variable. This research is a quantitative study using primary data, namely data taken directly from the answers of the respondents. The number of samples in this study were 100 respondents. By using data analysis methods in the form of data analysis techniques in which there are multiple linear analysis tests, hypothesis tests, path analysis tests and also the Sobel test. Data processing uses the IBM SPSS 23 application. The results of this study indicate that service quality has a significant effect on customer loyalty in using BSI Mobile. However, e-trust and digital transformation have no significant effect on customer loyalty in using BSI Mobile. The results of this study also show that customer satisfaction mediates a causal relationship between service quality, e-trust, and digital transformation on customer loyalty using BSI Mobile. Keywords: Service Quality, E-Trust, Digital Transformation, Customer Loyalty, Customer Satisfaction.